2018
DOI: 10.12693/aphyspola.133.959
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Co Ions Diffusion in Gd3Ga5O12 Single Crystals

Abstract: Spatial changes of properties of Gd3Ga5O12 (GGG) single crystals caused by diffusion of cobalt ions during high-temperature annealing (1200 • C, 24 h) in Co3O4 powder are investigated. The registration of these changes was carried out by optical spectrophotometry, microscopy and micro-Raman scattering methods. Changes in structure of near-surface layers of the crystal were investigated by X-ray diffraction technique. It was shown that the additional absorption induced by annealing is related to intra-center op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…This assumption is consistent with the results of work [ 11 ] on the study of cobalt diffusion into GGG crystals, where, using micro‐Raman scattering and local spectrophotometry methods, it was found that Co ions are incorporated into crystals to a depth of 600 µm.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This assumption is consistent with the results of work [ 11 ] on the study of cobalt diffusion into GGG crystals, where, using micro‐Raman scattering and local spectrophotometry methods, it was found that Co ions are incorporated into crystals to a depth of 600 µm.…”
Section: Discussionsupporting
confidence: 92%
“…This method was successfully used previously in the works dedicated to studies of optical properties changes caused by diffusion in lithium niobate and GGG single crystals. [ 11,13 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, positive modification of properties (optical, electrophysical) of surface and subsurface layers in LN and other oxide crystals by means of diffusion or implantation of metal ions is another important practical problem …”
Section: Introductionmentioning
confidence: 99%
“…In refs. [], the optical properties of reduced LiNbO 3 and cobalt‐doped Gd 3 Ga 5 O 12 , respectively, were studied along the diffusion direction, with a scanning light beam propagating parallel to the modified surface. These experiments have provided new information about a thickness of diffusion‐modified layers in crystals and a spatial distribution of induced point defects and dopant ions in the layers.…”
Section: Introductionmentioning
confidence: 99%